Optimal Portfolio Choice Under Incomplete Information: Discussion - Feldman, David (Journal of Finance, 1986)
David Feldman, Optimal Portfolio Choice Under Incomplete Information: Discussion, The Journal of Finance, Vol. 41, No. 3, Papers and Proceedings of the Forty-Fourth Annual Meeting of the America Finance Association, New York, New York, December 28-30, 1985 (Jul., 1986), pp. 747-749